Physico-Chemical Analysis of Solid Aerosols Generated from Different Industries of Faisalabad - Muhammad Attique Khan Shahid; Khadim Hussain; Maryam Saeed Awan (Journal of Basic & Applied Sciences, 2021)
The physical, chemical and electrical characteristics of industrial aerosols generated from different industries of Faisalabad were investigated not only to improve the industrial setup efficiency but also to reduce the environment pollution generated due to these industries. XRPD technique was employed to study these samples which showed the presence of illite, Quartz, calcite, dolomite, gypsum and chlorite as major phases. The values of resistivity of solid aerosols are in high range (0.07×107 to 4.0×109 ?m) conversely the electrical conductivities are in lower range (0.21-13.30Mho), may be due to high components of Fe2O3 and CaO. Coal fly ash and foundry aerosols do precipitate well in the electrostatic precipitator given their operational temperature and moisture content so it is recommended that by changing the temperature and moisture content of the precipitator its cleaning action and hence the industrial efficiency may be improved. The most of the solid aerosols are alkaline therefore acidic rain probability in near future is completely ruled out. 80% basic (Dark color), 20% acidic (light color) of particulate matter confirms our experimental findings. The SEM analysis of particulate matter showed the presence of a variety of patches but confirms the dominance of industrial cum transportational aerosols interlocking and soot particles. Finally comprehensive research and administrative based solution to tackle the issue without affecting the development process is suggested.